PENGEMBANGAN MODUL PRAKTIKUM IPA KELAS V BERORIENTASI HOME MATERIAL - Ni Nengah Persi; I Wayan Numertayasa; Ni Putu Eni Astuti (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
This research aims to determine the needs of teachers in carrying out practicum activities in class V with the Merdeka curriculum and to find out the prototype of home material-oriented practicum modules in class V at SD Negeri 1 Pengotan. This research uses quantitative descriptive methods and descriptive statistics with research design development to the expert validation stage. There are 5 stages in this research design, starting from the potential and problem stage, data collection, product preparation, product validation, product revision from validation results. The subjects of this research were students and teachers at SD Negeri 1 Pengotan with the object of development being a Home Material oriented Practicum Module. Validation carried out by experts came from ITP Markandeya Bali Lecturers. Module validation was analyzed with descriptive statistics using a Likert scale. The module design was approved with several revisions, including adjustments to the cover elements, the type of letters in the module for elementary school children and the assessment rubric which needed to be revised. The results obtained in research on the development of Home Material-oriented Practical Modules were categorized as very valid from the results of expert validation tests with an average score of 91.78% of the predetermined interval scale. The difference between this development research and previous development research can be seen from the content of the modules developed, resulting in differences in module validation scores. This is influenced by module validation standards that are adapted to the curriculum used.